Making Meaning of Religious Values in Preventing a Fatal Suicide Act of a Bisexual Youth with Borderline Personality Disorder: A Qualitative Study - Valentina, Tience Debora; Marchira, Carla R; Afiatin, Tina; Hadjam, Noor R (Jurnal Psikologi, 2021)
Male adolescents of sexual minority groups often present mental health problems and suicidal behaviors. This qualitative study was conducted to explore how a bisexual youth with borderline personality disorder and multiple suicide attempts coped with his intention to die. Analysis was done using the Grounded Theory approach resulted in several themes. First, the pathway to suicidal behaviors; depicting the conflict between parents and the history of mother’s suicide attempts made him felt disconnected with the family. Second, the feeling of not deserving loved although having the need to be loved and to love. Third, the ambivalence of his sexual orientations as he had strong desire to be with a man yet felt happy dating a girl. Fourth, the interpretation of religious values for preventing fatal suicidal act. He perceived that his suicide attempts failed because God wants him to stay alive. The discussion addresses the aspect of religiosity that obstructs suicidal behaviors in bisexual youths